455 Impact of EphB4 and PD-1 treatment on immune infiltrate in advanced bladder cancer. (10th December 2020) - Sadeghi, Sarmad; Hether, Tyler; Yeon, Jason; Mangio, Richard; Reeves, Jason; Liang, Yan; Warren, Sarah; McEachron, Troy; Gill, Parkash
Abstract : Background: Bladder cancer is the fourth most common cancer in American men with chances of 1 in 27 developing this form of cancer. Despite the progress in treating these patients with immunomodulatory agents, the vast majority of patients remain refractory to therapeutic intervention. EphB4 and EphrinB2 are induced in the tumor vasculature and modulate immune response within the tumor microenvironment. Intervention blocking Ephrin and PD-1/PD-L1 pathway has shown promising data in preclinical models. These data form the basis of clinical investigation of combined therapy in bladder cancer and other tumor types. Methods: Preclinical mouse models were treated with decoy soluble EphB4 and tumor infiltrating immune cells were profiled by RNA expression analysis post-treatment and compared to control treated mice. Next, patients were treated with soluble Eph4B in combination with anti-PD1 therapy, biopsies were obtained prior to and during the course of treatment. Biopsies were used for analysis of localized protein and RNA expression by GeoMx Digital Spatial Profiling (DSP). DSP analysis focused on tumor rich regions of interest (ROIs), adjacent stromal immune populations and microniches around vascular sites, with emphasis on sites where CD45+ T-cells were observed to be surrounding capillaries within and surrounding the tumor, presumably from extravasation. Results: In preclinical mouse models, EphB4 was found to induce several inflammatory pathways as a monotherapy including key immunomodulatory checkpoints such as PD1, PDL1, PDL2. Similarly, patients enrolled in this study were observed to have elevated T-cell infiltration in primary and secondary tumor sites, resulting in tumor mass reduction in post-treatment observations. DSP between matched samples discovered interesting differences in T-cell populations between both protein and mRNA expression. We observed evidence of tumor-debulking by decreased expression of epithelial markers such as Pan-cytokeratin and S100B within tumor ROIs, and increased infiltration within these ROIs measured by immune cell markers such as CD3 and CD163. Additionally, we observed increased GZMA expression post-treatment in perivascular regions suggestive of higher ongoing response by cells entering the tumor microenvironment. Additional analysis of localized RNA expression provided further support for activation of inflammatory cascades in post-treatment samples. Conclusions: These discoveries provide insights into the mechanism of action of EphB4 combination therapy in bladder cancer, providing support for a role of EphB4 acting as an adjuvant for PD1 therapy. Our results highlight the ability of EphB4 to activate the immune system both in preclinical models and in key structures within the tumor microenvironment during combination therapy. Trial Registration: NA Ethics Approval: The studies were approved by USC IRB Protocol 4B 15-11 and IACUC Protocol 20570.